Significance of blood pH value and automated external defibrillator shock in determining the outcomes of out-of-hospital cardiac arrest patients. Issue 2 (March 2018) - Tsai, Li-Heng; Chen, Chen-Bin; Liu, Peng-Huei; Chaou, Chung-Hsien; Huang, Chien-Hsiung; Kuo, Chan-Wei; Lin, Chi-Chun; Wang, Kuo-Cheng; Weng, Yi-Ming; Chien, Cheng-Yu
Background: The prognosis of out-of-hospital cardiac arrest is generally poor. It is known that the survival of out-of-hospital cardiac arrest patients depends on treatments delivered in a very short time frame. Identifying outcome-associated factors may provide valuable information for decision-making in clinical practices. Aim: The objective of the present study was to assess the associations between various factors (e.g. serum biomarker levels and prehospital factors) and outcomes in adult, non-traumatic out-of-hospital cardiac arrest patients. Methods: Data from 386 consecutive out-of-hospital cardiac arrest patients treated from January 2012 to December 2015 at Taoyuan Chang Gung Memorial Hospital (Taiwan, ROC) were collected. While performing cardiopulmonary resuscitation in the emergency room, the levels of creatinine, aspartate aminotransferase, sodium, potassium, troponin-I, hydrogen bicarbonate and haemoglobin were determined, blood pH and pCO2 were measured and the white blood cell count was calculated. The response time and scene time interval were also recorded. Results: Here we found that out-of-hospital cardiac arrest patients with blood pH values of <7.34 had a lower chance of survival to 24 h (Odds Ratio (OR) = 2.77), survival to discharge (OR = 7.06) and a good neurological outcome (OR = 64.59). Moreover, patients without an automated external defibrillator shock had a lower chance of being discharged (OR = 4.27) and enjoying good neurological outcomes (OR = 25.09). Conclusion: Our data suggest that the blood pH and an automated external defibrillator shockable rhythm are two easily measurable factors strongly associated with the outcomes of out-of-hospital cardiac arrest patients.